Developing Science Comic Learning Media for Grade IV Elementary School Based on Local Wisdom of South Kalimantan - Ria Mayasari; Lili Agustina; Rifki Maulana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research aimed to; 1) determine the feasibility of comic-based learning media based on the local wisdom of South Kalimantan for the science subject in grade IV elementary school; 2) determine the responses of teachers and students to comic-based learning media based on the local wisdom of South Kalimantan for the science subject in grade IV elementary school. This research used Research and Development (R&D) with the Four-D (4D) development model; Define, Design, Develop, Disseminate. The trial design took the form of validation sheets and questionnaires with research subjects consisting of a media validator, a material validator, a language validator, teachers, and students of SDN Pengambangan 6 Banjarmasin. Data analysis was conducted after collecting data from the results of expert validation and the responses of teachers and students. The results showed that the feasibility from media experts was 93.3% (very feasible). The feasibility from material experts was 83.3% (very feasible). The feasibility from language experts was 94.3% (very feasible). The average feasibility assessment by the three expert validators for comic-based learning media based on the local wisdom of South Kalimantan was 89.2%, categorized as very feasible. The teacher response assessment result was 86.6% with a criteria of very good, and the student response assessment result was 78.75% with a criteria of good.